Influence of environmental parameters on habitat preference of gelatinous zooplankton in various coastal ecosystems, the Straits of Malacca - Abd Razak, Siti Balqis; Md. Yusoff, Fatimah; Nishikawa, Jun; Lindsay, Dhugal; Nishida, Shuhei (Elsevier, 2019)
This study examined spatial distribution patterns of gelatinous zooplankton in three coastal areas, namely Matang mangrove area (managed mangrove area, MMA), Kuala Selangor coastal waters (reclaimed mangrove area, RMA) and Port Dickson coastal waters (a resort area, PDC). In each area, non-gelatinous and gelatinous zooplankton samples were collected by horizontal tows of a plankton net (140 um mesh size) and a Bongo net (500 um mesh size). Various environmental parameters were measured in situ (temperature, dissolved oxygen, pH, turbidity) as well as analyzed in the laboratory (nutrients, chlorophyll-a , zooplankton). Nineteen hydromedusae, two siphonophore and two ctenophore species were recorded from three different areas. Matang mangrove (MMA) had the highest number of species (19 species), followed by RMA (13 species) and PDC (9 species). Gelatinous zooplankton density and biomass were significantly higher (p < 0.05) in MMA than the other areas. Different gelatinous zooplankton groups dominated in different areas with ctenophores as the most important group (Pukia sp. formed 79.0% of total gelatinous zooplankton) in MMA. The hydromedusae (55.0% was Eirene brevigona) was the most dominant group in RMA that had high total suspended solids, and siphonophores (58.0% was Lensia subtiloides) dominated PDC characterized by high water transparency. Biotic-environmental (BIO-ENV) analysis showed significant roles of turbidity, salinity, nutrients, chlorophyll-a and non-gelatinous zooplankton (p < 0.05) in the distribution of gelatinous zooplankton in these tropical coastal ecosystems. Two-way ANOSIM (analysis of similarities) showed that there were significant differences in gelatinous zooplankton amongst the three habitats. In terms of monsoonal seasons, the gelatinous zooplankton density showed significant differences (p < 0.05) between the southwest and northeast monsoons. This study illustrated that gelatinous zooplankton diversity and density varied with the degrees of habitat disturbance and seasonal changes, implying the potential impacts of anthropogenic activities and climate change on its community structure